2021
DOI: 10.1002/ese3.953
|View full text |Cite
|
Sign up to set email alerts
|

Bionic coupling design and aerodynamic analysis of horizontal axis wind turbine blades

Abstract: With millions of years of evolution, owls have developed many excellent characteristics in terms of their flight. The speed of an owl in flight is similar to the relative speed of the blade of a small wind turbine with respect to air. Therefore, the owl wing airfoil is selected as the design airfoil of the wind turbine blade to reduce the flow separation under low Reynolds number. In this study, we analyze an owl wing‐section airfoil and the non‐smooth leading‐edge shape of an owl's wing, and implement an orth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Owls require a significant amount of lift to glide silently and evade detection by their prey. As a result, the airfoil structure of owl wings has been extracted and applied in the design of wind turbine blades to enhance their performance [177].…”
Section: Owl Guillemot Seagull Albatros Stork and Golden Eaglementioning
confidence: 99%
See 2 more Smart Citations
“…Owls require a significant amount of lift to glide silently and evade detection by their prey. As a result, the airfoil structure of owl wings has been extracted and applied in the design of wind turbine blades to enhance their performance [177].…”
Section: Owl Guillemot Seagull Albatros Stork and Golden Eaglementioning
confidence: 99%
“…The study revealed several remarkable features of owl feathers, including a comb-like structure along the leading edge, a fringe-like arrangement along the trailing edge, and soft down feathers on the wings and legs. These unique feather structures enable owls to glide and fly silently, setting them apart from other birds [177]. Ito [179] studied the aerodynamic influence of leading-edge serrations on an airfoil at low Reynolds numbers.…”
Section: Owl Guillemot Seagull Albatros Stork and Golden Eaglementioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, biomimetic technologies inspired by various biological characteristics have emerged as promising approaches for enhancing wind turbine blade design [15]. For example, to reduce the flow separation on blade surfaces, an owl wing-section airfoil and the non-smooth leading-edge shape of owl wings were studied in [16], finding that the power coefficient of the wind turbine can be increased by 17.7% by optimizing the wavelength and amplitude of the non-smooth leading edge of the blade. Inspired by the distinctive profile of the owl wing and the herringbone groove feature of owl feathers, the blade of a 200 W horizontal axis wind turbine was redesigned [17].…”
Section: Introductionmentioning
confidence: 99%